Czego powinni nauczyć się filozofowie i czego mogą oni nauczyć innych? - Drozdowicz, Zbigniew (Bydgoski Oddział Polskiego Towarzystwa Filozoficznego Filo-Sofija, 2014)
What Philosophers should Learn and What Others Could Learn from Them? The remarks presented here are being outlined given a very simple and straightforward contention that to teach someone something important we have to learn it first. It has been a certain problem not just for philosophers. However, I refer here only to the latter, not just because teaching and learning is more problematic for them than the others, but because their academic teaching nowadays undergoes an apparent crisis of trust and – which is connected with it anyway – because of the interest shown by the candidates for students. The causes thereof are of course different, including these which cannot be affected by the philosophers themselves. Yet there are also those which can be and are affected in a significant manner. They include, to my mind, the creating of the positive picture of philosophy and philosophical thinking. This has been a troublesome issue. However, my standpoint is that we cannot expect this crisis of academic teaching to end in the situation in which the philosophers speak of philosophy itself negatively rather than vice versa.
Keywords: academic teaching; philosophical traditions; criticism; rationalism; sophistic